A novel two-layer periodic stepped structure for effective broadband radar electromagnetic absorption. (5th June 2017) - Zhou, Qian; Yin, Xiaowei; Ye, Fang; Liu, Xiaofei; Cheng, Laifei; Zhang, Litong
Abstract: This paper presents a novel ultra-broadband two-layer periodic stepped radar absorbing structure (PSRAS). The optimal PSRAS shows more than 90% absorption in the frequency range from 2.64 to 40.0 GHz by using a conventional α Fe reinforced epoxy resin composite. The greatly enhanced radar absorption property of designed PSRAS is a result of the multi-scale effect by combing effects of microscopic and mesoscopic scales. The designed PSRAS makes the effective impedance match to that of the free space in a wide frequency: most of the incident energy is dissipated by the simultaneous incorporation of multiple λ /4 resonances, strong resonances between adjacent unit cells and edge diffraction effects. Based on the geometrical parameters optimization for the two-layer PSRAS, it is specified that size of unit cell obeys a simple rule of the Golden Section approximately. Additionally, the incident angle dependent absorption properties are simulated and discussed. It is expected that the proposed PSRAS composite has great potentials in stealth technologies and electromagnetic interferences. Graphical abstract: Highlights: The designed two-layer periodic stepped absorbing structure has more than 90% absorption from 2.64 to 40 GHz frequency. Resonances between adjacent unit cells and edge diffraction effects lead to a great absorption. The two-layer periodic stepped absorbing structure can achieve great absorption when incident angles is less than 45°.